Rancang Bangun Sistem Jual Beli Online dengan Pendeteksi Produk Pakaian Menggunakan Scan QR Code - Saputri, Aulia Kintan; Handoko, Slamet; Triyono, Liliek (Teknik Elektro - Politeknik Negeri Semarang, 2018)
Lullabyworks is a clothing manufacturer located on Jalan Pusponjolo Selatan Semarang. Lullabyworks produces and sells various clothes ranging from t-shirt, jacket, sweater, hoodie etc. Lullabyworks entrusts its products to one of the distros in Semarang and uses COD (Cash on Delivery) system to market its products. In the current sales system there are two disadvantages that customers have difficulty knowing the stock of goods, and difficulty in ordering goods, especially for customers who are outside the city of Semarang. This reasearch aims to develop an online shopping system with the detection of clothing products using QR Code scans. This system has features to order goods, QR Code scan to check the product, and can record the sale and stock of goods. The research method is the waterfall methodology, in this methodology every step of the final task is done in sequence, starting from design, analysis, design, implementation, to treatment. The result show that all existing features and menus have run in accordance with its function and no errors occured. The results of the questionnaire satisfaction rate of prospective customers and admin shows that the satisfaction level of 79.6% which means feeling very satisfied. From the results of system evaluation conducted the system is able to produce a system with features for ordering goods, searching goods using QR Code scan and display records sales and stock of goods.Keywords : Online shopping, QR Code